Changes in platelet parameters and secondary brain injury in acute craniocerebral trauma - Xiaoping Tang Chao You Hua Peng Tao Zhang Wenguo Tang Jian Qi Renguo Luo Yuanchuan Wang Ling Feng Zhangyang Gou Junwei Duan Shun Li (中国神经再生研究（英文版）, 2011)
Changes in platelet parameters are important in secondary brain injury in acute craniocerebral trauma We selected 163 patients with craniocerebral trauma who were admitted within 24 hours with nonoperative therapy. Platelet parameters of 40 healthy subjects served as controls. Platelet number was decreased, while mean platelet volume and platelet distribution width values were increased, at 1 and 3 days after injury. Platelet number was lower and mean platelet volume and platelet distribution width were larger in patients with traumatic cerebral infarction and those in Glasgow Coma Scale score 〈 8 group. Platelet number was negatively correlated to volume of cerebral edema, but positively correlated to Glasgow Outcome Scale score. These data indicate that changes in platelet parameters may be utilized to indicate the state of central nervous system injury and patient prognosis .